The visual perception of phrasing in a tai chi routine enhanced by music as perceived by inexperienced viewers - Loo, Fung Chiat; Loo, Fung Ying (2017)
Phrasing is one of the most important features shared by music and a movement-oriented subject such as dance, or any sports routine that involves a choreography. As a pilot study to investigate the perception of inexperienced viewers, this study investigates whether an increased level of congruence between music and movement will enhance the visual perception of phrasing in a Tai Chi routine. A Tai Chi practitioner, who was expert in the exercises and a medallist in numerous reputed competitive events, was engaged. A competitive sword routine with the original music accompaniment used by the practitioner was selected in this experiment and the performance of the routines was recorded. A new accompaniment was composed for the same routine where the congruence between music and movement was increased from a musical perspective. Thirty viewers (N=30) without any background in music, sports or dance were invited to participate in the survey, and asked to rate the level of phrasing quality of the two videos, one with the original accompaniment and the other with the new composition. Although the survey did not show a significant difference between the perceived phrasing in the two videos, the video with the new accompaniment still recorded a higher rating on overall phrasing and sword movements. This correlates with the previous report (Loo & Loo, 2015) from the same project where viewers with a musical background significantly rated the video with new accompaniment as having a better quality of phrasing.